Using Inquiry-Based Strategies for Enhancing Students’ STEM Education Learning - Ching-San Lai (Journal of Education in Science, Environment and Health)
The major purpose of this study was to investigate whether or not the inquiry-based method is effective in improving students’ learning in STEM (Science, Technology, Engineering, and Mathematics) education. Both quantitative and qualitative methods were used. A total of 73 college students studying Information Technology (IT) were chosen as participants. The instructional strategy used in this study was inquiry-based instruction. Participants were asked to answer a course satisfaction survey which utilized a 5-point Likert-type scale (a grade of 1 for least satisfied and 5 for highly satisfied); data obtained underwent means analysis. In addition, qualitative data including students' learning feedback and instructors’ teaching feedback were collected and analyzed. The findings of this study includes: (1) students were highly satisfied on the STEM education learning program used in this study; (2) students’ learning feedback also showed that they approved inquiry-based learning; and (3) instructors’ teaching feedback showed that they preferred inquiry-based instruction as a teaching method. It can be concluded that the use of inquiry-based instruction can improve college students’ STEM education learning.